PENERAPAN PROGRAM BAHASA ARAB DALAM PEMBELAJARAN MAHARAH AL KALAM DI SMA IT INSAN MULIA BOARDING SCHOOL PRINGSEWU, LAMPUNG: Indonesia - Toponi, Meizar; Aulia, Maya; Masrur, Mohammad (STIT Pringsewu, 2023)
AbstractIn the context of learning Arabic, mahārat al-kalām is the main skill that must be mastered by students and is one of the ultimate goals of learning a foreign language. The mahārat al-kalām learning course at SMAIT Insan Mulia Boarding School Pringsewu Lampung has not shown results that describe students' Arabic language skills actively and productively. In accordance with the background of the problems described above, the authors formulate the problem in this paper is